Classroom observation its use by public school division supervisors in Cagayan - Liban, Pura (Tumada) 1923- (s.n.], 1964)
This study determines the status of classroom observation as a supervisory technique based on the practices of the division supervisors in Cagayan. It identifies the strengths and weaknesses of this supervisory technique as used by a particular group of supervisors. This also serves as a pace-setter in starting a series of similar studies in order to evolve a set of criteria for evaluating classroom observation as a supervisory technique which is indigenous to the Filipino Culture and to prevailing conditions in the country.